Factors associated with dental hospitalisations in children with intellectual disability or autism spectrum disorder: a Western Australian population-based retrospective cohort study. Issue 19 (11th September 2022) - Azimi, Somayyeh; Lima, Fernando; Slack-Smith, Linda; Bourke, Jenny; Calache, Hanny; Junaid, Mohammed; Leonard, Helen
Abstract: Purpose: This study investigated dental hospitalisations in Western Australian (WA) children with intellectual disability (ID) and/or autism spectrum disorder (ASD) aged up to 18 years. Methods: Data on WA live births from 1983 to 2004 from the WA Midwives Notification System were linked to the Intellectual Disability Exploring Answers database, the WA Hospital Morbidity Data System, and the Western Australian Birth Defects Registry databases. Children were followed from birth to 2010 and the data grouped into three age-groups. Primary and secondary admissions for relevant dental diagnoses were identified and factors associated with having a dental hospitalisation investigated. Results: There were 1366, 1596, and 780 dental hospitalisations amongst 1122, 1154, and 609 children with ID and/or ASD in the 0–6, >6–12, and >12–18 year age groups, respectively. Children with severe ID were much more likely to be hospitalised than those with mild/moderate ID. More socioeconomically disadvantaged children were less likely to be hospitalised than children whose parents were socially advantaged. Conclusions: There is concern that more vulnerable children in the WA community with ID or ASD are receiving an inadequate level of dental services compared with other groups resulting in potentially preventable hospitalisations, a situation in need of urgent remediation. Implications for rehabilitation: Little is known about why some children with intellectual disability (ID) or autism are being hospitalised for their dental care and others are not. Children with disability whose families are socioeconomically disadvantaged should have equivalent opportunity to receive optimal dental care. Dental practitioners at all levels need training and confidence in treating children with ID.